O MONGOLSKICH NARUSZENIACH POGRZEBOWYCH, GRACH WESELNYCH I BARANICH KOŚCIACH. STUDIUM SYMBOLIKI TRUDNEJ - Jerzy S. Wasilewski (Etnografia Polska, 2015)
Among the Torghuts of Western Mongolia, some elaborated forms of rituals like wedding and funeral, although discontinued, are still remembered in detail, while their symbolism is forgotten. In the wedding games – being a set of five playful competitions between the bride givers and takers – the process of gradual acquisition of social roles of the bride/wife by the groom’s side is demonstrated, whereas the contested objects (a sheep tibia bone, a carpet, a goat skin etc.) are symbols of her kin group affiliation, her dowry, and her place in the new household, respectively. The games, being a series of mock-refusals and takeovers, with their intrinsic retardations, provide an embodied experience of a gradual passage of the bride, commemorating this event in the social memory